2m+10=16

Simple and best practice solution for 2m+10=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+10=16 equation:


Simplifying
2m + 10 = 16

Reorder the terms:
10 + 2m = 16

Solving
10 + 2m = 16

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 2m = 16 + -10

Combine like terms: 10 + -10 = 0
0 + 2m = 16 + -10
2m = 16 + -10

Combine like terms: 16 + -10 = 6
2m = 6

Divide each side by '2'.
m = 3

Simplifying
m = 3

See similar equations:

| Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 | | 5y+2(y-4)=5(y+1)-2 | | 4(y+1)+5=(y-1)+y | | -3x-6y=17 | | 6x+10=x+25 | | 8x-(2x+4)=38 | | z+15=20 | | -2(n-1)=3-2n | | 5x+2=x-2 |

Equations solver categories